PHILOSOPHICAL PEDAGOGIC OF H.S. SKOVORODA: RESPOND ON SOCIETY CHALLENGES IN THE MODERNITY - Култаєва, Марія (New Collegium, 2020)
The article is devoted to the reconstruction of the philosophical pedagogics of H.S. Skovoroda which is regarded as an original respond on society challenges emerging in the Ukraine contexts in the XVIII century. The ontological frames of the educational practices are analyzed, which demonstrate contradictions between needs of modern urban culture and old values determinate by the real existing feudal contexts. The philosophical pedagogic developed by Skovoroda might be regarded as a contribution to establishment culture of freedom, which had tried to give some new orientations for the development of human being and society.